Fall Prediction and Prevention System using a Technology: A Literature Review - Kartika Mawar Sari; Hanny Handiyani (International Journal of Nursing and Health Services (IJNHS), 2020)
Incidence of patients falling in hospitals is a serious problem because it is one of the indicators of patient safety. Prevention of patients falling with technology has done a lot in the service and has a positive impact. The technology used is quite diverse, ranging from the use of interactive applications, static to virtual reality (VR). This literature study aims to analyse the benefits of using technology in preventing falling patients in health care. The results of the study show that the use of technology in preventing falling patients has proven to be quite effective in reducing falling patients. The use of technology to prevent falling patients, especially in hospitals, is important to apply because it has a positive impact on improving services to patients, improving quality and decreasing costs in hospitals, with the use of technology to prevent falling patients, the incidence of falling patients can be reduced and services provided to be safe and efficient.